Higenamine Attenuates Doxorubicin-Induced Cardiac Remodeling and Myocyte Apoptosis by Suppressing AMPK Activation - Jin, Cuiliu; Chai, Yu; Hu, Zhimin; Tian, Wencong; Ling, Wang; Li, Jing; Wu, Meiping (Frontiers in Cell and Developmental Biology, 2022)
Background: As an effective anti-tumor drug, Doxorubicin (Dox) is mostly used to treat solid tumors and hematologic malignancies. However, increasing evidence emerged indicated its cardiotoxicity, moreover, few treatments provided to solve this side effect. Higenamine (HG) is a natural compound, widely found in many Chinese herbs, also serves as a component in many health care products, researches, including our own, demonstrate its cardioprotective effect in different models. But little is known about the underlying influences of HG against myocardial on Dox-induced chronic cardiotoxicity. Methods and Results: C57BL/6 mice and neonatal rat ventricular myocytes cardiomyocytes (NRVMs) were used to evaluate the cardioprotective effect of HG against Dox-induced myocardial damage. In mice, Dox (intraperitoneally injected 5 mg/kg/3days for 4 weeks) significantly increased cardiomyocyte apoptosis, cardiac atrophy and cardiac dysfunction, which were significantly attenuated by HG (intraperitoneally injected with 10 mg/kg/day for 4 weeks). In NRVMs, DOX (3μM for 24 hours) significantly increased cell apoptosis and the level of ROS, reduced the level of SOD and mitochondrial membrane potential, HG can remarkably resume these pathological changes. Interestingly, the protect effect of HG on Dox-induced cardiotoxicity was independent of the activation of the beta2 adrenergic receptor (β2-AR) that is known to mediate the effect of HG on antagonizing ischemia/reperfusion induced cardiac apoptosis. Furthermore, HG attenuated abnormal elevation phosphorylated adenosine activated protein kinase (AMPK), consistently, AMPK agonists (AICAR) can eliminate all these pharmacological actions of HG. Conclusion: Collectively, our result suggested that HG alleviated the DOX-induced chronic myocardial injury by suppressing AMPK activation and ROS production.